Building Citizen Satisfaction with E-Government Services: A Case Study of the Population Administration Information System (SIAK) - Ramadhan, Sukma Aditya; Pribadi, Ulung (Universitas Padjadjaran, 2024)
In the era of globalization and digital transformation, e-government has become the main strategy for the government to improve public services. Despite progress, citizen satisfaction remains important. This research focuses on Indonesia's Population Administration Information System (SIAK). Using a quantitative research design and Structural Equation Modeling (SEM-PLS), we analyzed factors such as trust in the government, its perceived usefulness, perceived quality of electronic services, and digital literacy. Our findings show that digital literacy and the quality of electronic services significantly affect citizen satisfaction. Trust in the government has a positive effect but is not significant. To increase citizen satisfaction, Indonesia must prioritize improving digital literacy and the quality of electronic services. This will ensure that e-government initiatives effectively meet the needs and expectations of its citizens.